OPTIMALISASI MANAJEMEN RISIKO KEUANGAN (FINANCIAL RISK MANAGEMENT) SEBAGAI UPAYA STABILITAS PEREKONOMIAN - Siwi, Puput Ranu; Natasia, Bella; Salsabilla, Nurhanifah; Putri, Retno Karunia; Hanifah, Umi (Ekonomi dan Bisnis, 2024)
Competition in the business world is one phenomenon that cannot be avoided in the economic sphere. Strength and resilience in competition in a strong trade market can have a positive impact on the economy so that the economy grows positively. The approach to the study of this article is a literature review study using the systematic literature review (SLR) method. Data collection method using literature study. The data analysis technique uses a qualitative descriptive method. The results and discussion of the review of this article is that financial risk management is an of efforts to achieve economic stability where through good financial risks management it can have a positive impact on the economy so that the economy can grow stably and can provide opportunities to remain competitive in the global market.   Keywords: Financial Risk Management; Economic Growth; Economic Stability.